FORECASTING AIR POLLUTION DRIVEN BY VEHICLE GROWTH, PUBLIC TRANSPORT, INDUSTRY, AND HOUSEHOLD WASTE - Harjono, Chandra; Gianto, Ludy; Sidik, Rachmattullah; Widaningrum, Dyah Lestari (UI Scholars Hub, 2024)
Jakarta, Indonesia's bustling capital, is grappling with escalating air pollution levels attributed to a confluence of socio-economic and infrastructural factors. This study employs Vensim modelling to project PM2.5 pollution trends through 2040, analysing the dynamic interplay among major contributors: increased vehicular emissions, industrial activities, public transportation deficiencies, and waste management inefficiencies. Materials and Methods: The method that will be used in this air pollution analysis is to integrate empirical data spanning three years to construct a predictive model underpinned by a robust causal loop diagram that elucidates the relationships between system variables and air quality. The results of this paper indicate a projected 50% increase in PM2.5 levels by 2040 if current trends persist, with vehicular emissions being the predominant contributor, accounting for 67.4% of the increase. This underscores the critical need for stringent emissions standards and comprehensive enhancements to public transportation infrastructure. The study's simulations suggest that without significant policy interventions, air quality will continue to deteriorate, posing severe public health risks. Discussion points emphasise the model's implications for environmental policy, advocating for targeted measures to curb vehicular emissions and promote sustainable urban planning. Comparisons with existing literature highlight the study's contribution to understanding localised pollution dynamics, providing a granular analysis that aligns with global research trends. This paper aims to call for immediate action to implement rigorous environmental policies and infrastructure improvements to mitigate air pollution effectively. These strategies include enforcing stricter emissions standards, expanding public transportation networks, and integrating sustainable technologies across transportation and industrial sectors. This research not only maps a trajectory of Jakarta's air quality but also frames a policy response model that could guide similar urban centres globally facing air pollution challenges.